GANGGUAN HUMUS HUTAN DI TAHURA YANG BERBATASAN DENGAN LAHAN PERTANIAN MASYARAKAT, DESA DOLAT RAYAT KABUPATEN KARO - Bangun Sikettang; Budi Utomo; Afifuddin Dalimunthe (Program studi Kehutanan USU, 2015)
The forest is seen as an ecosystem, because forest is formed or composed by many components, each component can not stand on its own, can not be separated, even interplay and interdependence. One component forests have an important role to the availability of nutrient cycling in the forest is humus. Humus is part of the composition of the forest has its own function in maintaining the balance of nature. Without humus, then the forest will lose its function in maintaining the stability of the hydrological cycle and soil nutrient cycling. Accordingly, this research aims to detect differences in the thickness of humus at a distance of 0-500 m of agricultural land society, to determine the distance to the forest by forest communities Dolat Rayat villages, districts of Karo, and determine the impact of forest humus decision on vegetation For seedling and saplings. This research showed that the availability (thickness) humus in Forest Park (TAHURA) bordering agricultural land within the community is varied from 0-500 m and impaired. Withdrawal of forest humus reaches a distance of 250 m, and humus began to stabilize in thickness at a distance of 350 m into the forest. Withdrawal of humus also affects the amount and type of vegetation growing in the forest so that species diversity of an area to be low. In areas that do not damage the forest and humus disturbance to the number of individuals, and higher species diversity. Keywords: Forest Humus, Vegetation, Nutrient Cycle, Agricultural Land, Society